Sensors and Smart Structures Technologies for Civil, Mechanical, and Aerospace Systems 2021 2021
DOI: 10.1117/12.2582457
|View full text |Cite
|
Sign up to set email alerts
|

Active scour monitoring using ultrasonic time-domain reflectometry to detect a soil interface

Abstract: Local scour is arguably the most pressing issue regarding the safety and longevity of overwater civil infrastructure. Many modern scour detection techniques do not provide continuous scour depth measurements, nor can they function under extreme flow conditions, which is when scour monitoring becomes most critical. Thus, the objective of this study was to develop scour depth monitoring sensors using ultrasonic time domain reflectometry (UTDR). The scour sensor was based on an aluminum strip with two piezoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Previous Lamb wave UTDR work by Funderburk et al [27] validated that an applied metal interface produced a detectable reflected wave response that varied according to the location of the interface. This previous study, however, was performed using an aluminium strip, which is lower in stiffness and could be more sensitive to localized pressure from to a weaker pressure interface, such as soil.…”
Section: Sensor Designmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous Lamb wave UTDR work by Funderburk et al [27] validated that an applied metal interface produced a detectable reflected wave response that varied according to the location of the interface. This previous study, however, was performed using an aluminium strip, which is lower in stiffness and could be more sensitive to localized pressure from to a weaker pressure interface, such as soil.…”
Section: Sensor Designmentioning
confidence: 95%
“…UTDR for scour monitoring will be unique in that the propagating medium does not need to have any permanent damage, but rather impedance changes will stem from where the surrounding soil interface is in contact with the buried sensing strip. Funderburk et al [27] showed that Lamb waves are sensitive to external pressures that interact with the surface. To detect scour, Lamb waves are propagated down the length of a thin strip, which is essentially a plate that is much longer than its width.…”
Section: Utdr For Scour Depth Monitoringmentioning
confidence: 99%
See 1 more Smart Citation